Ethnobiology Study on Seasonal Variation of Forage Plant at Ruminansia Livestock Production Center - Dewi, NT.; Arisoesilaningsih, E.; Soebarinoto, Soebarinoto (Sainsmat : Jurnal Ilmiah Ilmu Pengetahuan Alam, 2017)
This study aims to determine seasonal variations livestock forage plants in several centers of animal production Cattle and Goats. The method used in this study was the observation by ethnobiological approach in several production centers ruminant livestock (cattle and goats) in East Java and Southeast Sulawesi. The results showed that the number of food plants live in the rainy season more than the dry season.The decline in the number of plant species are more common in plants than the annual grass perennial broadleaf plants.The largest decline in the number of plant species forage due to drought occurred in Pamotan district. Dampit and Langgea, otherwise only slight changes in Ringinsari and Malang.